2011
DOI: 10.1176/appi.ps.62.11.1296
|View full text |Cite
|
Sign up to set email alerts
|

A Web-Based Program to Empower Patients Who Have Schizophrenia to Discuss Quality of Care With Mental Health Providers

Abstract: Objective This study evaluated a Web-based tool to help patients with schizophrenia communicate with clinicians about evidence-based treatments. Methods Fifty patients used an interactive Web-based intervention featuring video clips of actors simulating a patient discussing treatment concerns (intervention group; N=24) or were shown an educational video about schizophrenia treatment before a routine follow-up appointment (control group; N=26). The visits were recorded and analyzed by using the Roter Interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 15 publications
0
11
1
Order By: Relevance
“…However, they contradict the findings by Hamann et al [3] and Steinwachs et al [13] who found a positive effect of decision aids on patients’ involvement in consultations with their clinicians. This discrepancy can be explained by several reasons.…”
Section: Discussioncontrasting
confidence: 78%
See 3 more Smart Citations
“…However, they contradict the findings by Hamann et al [3] and Steinwachs et al [13] who found a positive effect of decision aids on patients’ involvement in consultations with their clinicians. This discrepancy can be explained by several reasons.…”
Section: Discussioncontrasting
confidence: 78%
“…In our study, patients could use the decision aid either in the clinic or at home, with or without assistance, whereas in the trial by Hamann et al [3], patients used the decision aid in a psychiatric ward with assistance of trained nurses. The setting in the study by Steinwachs et al [13] was not described. Third, our response rate was very low.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Computerized interventions for schizophrenia have already made good use of videos to relay psychoeducational information or depict training roleplays in supervised clinic settings (Gottlieb et al, 2013; Steinwachs et al, 2011). The study adds to these findings and suggests that video interventions may be a feasible, usable, acceptable, and highly engaging method for more flexible delivery of interventions to people with schizophrenia using mobile technology outside of the controlled clinic environment.…”
Section: Discussionmentioning
confidence: 99%